2016
DOI: 10.1016/j.celrep.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Development of Cytotoxic and Follicular Helper CD4 T Cells Controlled by the TCF-1-Bcl6 Nexus

Abstract: SummaryCD4+ T cells develop distinct and often contrasting helper, regulatory, or cytotoxic activities. Typically a property of CD8+ T cells, granzyme-mediated cytotoxic T cell (CTL) potential is also exerted by CD4+ T cells. However, the conditions that induce CD4+ CTLs are not entirely understood. Using single-cell transcriptional profiling, we uncover a unique signature of Granzyme B (GzmB)+ CD4+ CTLs, which distinguishes them from other CD4+ T helper (Th) cells, including Th1 cells, and strongly contrasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 45 publications
(101 reference statements)
9
62
0
Order By: Relevance
“…We also observed upregulation of Cd8a gene expression, although at very low expression levels (FPKM < 0.5) ( Figure 2C), correlating with the undetectable or low-level CD8α protein expression determined by flow cytometry ( Figure 1D). Moreover, in agreement with a study showing opposing development of CD4 + cytotoxic T cells and T follicular helper cells (18), BCL6 signatures were downregulated, and Blimp-1 (encoded by Prdm1) signatures ( Figure 2B) as well as Prdm1 expression ( Figure 2C) were upregulated. To obtain an understanding whether expression signatures in HDAC1 cKO -HDAC2 HET CD4 + T cells represent Th1-like or CTL lineage patterns, we performed gene set enrichment analyses (GSEAs).…”
Section: Resultssupporting
confidence: 91%
“…We also observed upregulation of Cd8a gene expression, although at very low expression levels (FPKM < 0.5) ( Figure 2C), correlating with the undetectable or low-level CD8α protein expression determined by flow cytometry ( Figure 1D). Moreover, in agreement with a study showing opposing development of CD4 + cytotoxic T cells and T follicular helper cells (18), BCL6 signatures were downregulated, and Blimp-1 (encoded by Prdm1) signatures ( Figure 2B) as well as Prdm1 expression ( Figure 2C) were upregulated. To obtain an understanding whether expression signatures in HDAC1 cKO -HDAC2 HET CD4 + T cells represent Th1-like or CTL lineage patterns, we performed gene set enrichment analyses (GSEAs).…”
Section: Resultssupporting
confidence: 91%
“…However, it is also possible that CD4 þ CTLs may comprise a distinct, independent subset of CD4 þ effector T cells that differ from conventional Th1 cells (10). Indeed, several recent reports have identified specific markers for CD4 þ CTLs (11)(12)(13)(14). Interestingly, Eomes is expressed in many of the cells expressing these markers, as well as in other CD4 þ T cells with cytolytic properties (15)(16)(17)(18); these findings suggested that Eomes governs development of CD4 þ CTLs and that Eomes expression is a marker for CD4 þ CTLs.…”
mentioning
confidence: 99%
“…Tfh cells interact with B cells in the specialized areas of lymph nodes and spleens called germinal centers where the processes of somatic hypermutation and isotype switching occur. It has been shown that tumor infiltrating Tfh cells may help to maintain CTLs at tumor sites, though they do not differentiate into cells that produce cytotoxic granules [3436]. Therefore, if the function of the bull’s eye synapse is solely the delivery of cytolytic granules, Tfh, like Th2 cells, may have a multifocal synapse structure.…”
Section: Discussionmentioning
confidence: 99%